Cr3+ doped Al2O3 obtained by non-hydrolytic sol-gel methodology - Caiut, José M.A.; Floch, Nolwen [UNESP]; Messaddeq, Younès [UNESP]; De Lima, Omar J.; Rocha, Lucas A.; Ciuffi, Katia J.; Nassar, Eduardo J.; Friedermann, Geraldo R.; Ribeiro, Sidney J.L. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2019)
This paper reports the synthesis and characterization of Cr3+-doped alumina by the sol-gel non-hydrolytic methodology. The resulting sample was treated at different temperatures. X-ray diffraction revealed that the ruby phase emerged in the sample treated at 1100 oC, which was later confirmed by absorption bands correspondent to Cr3+ ions allowed transitions at 4A2 → 4T1 4T2, and forbidden at 4A2 → 2T1 2E, observed by diffuse reflectance UV-Vis. The luminescence spectroscopy showed the intensity band at 694 nm in red region, characterized of the Cr3+ ion. The peaks at 702 and 705 nm correspond to N1 and N2 lines, respectively, which arose from the second and fourth nearest-neighbor exchange-coupled pairs of chromium(III) ion, respectively, ascribed to high chromium(III) concentration. The Cr3+ cluster formation was observed in electron paramagnetic resonance signal as discussed in this work. Nuclear magnetic resonance evidenced that the 27Al symmetry changed in the samples treated between 900 and 1100 oC.
Keywords: EPR; Luminescence; NMR; Ruby; Sol-gel